Peran Analisis Swot dalam Upaya Penyusunan Strategi Bisnis Usaha Kecil dan Menengah di Kabupaten Tuban - Siswoyo; Nur Hidayatul Istiqomah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The industrial revolution encourages individuals to think critically and creatively in implementing entrepreneurship, especially through micro, small, and medium enterprises (UMKM), which are currently promising business potential. The rapid growth of UMKM increases competition in Tuban Regency, encouraging the need for a business strategy that can provide a competitive advantage. This qualitative research uses interviews and literature studies to gather appropriate facts. Results of the analysis SWOT shows that UMKM in Tuban Regency are in Quadrant I, indicating a great opportunity that can be utilized with their strengths. The implemented strategy supports aggressive growth, allowing UMKM to maximize their potential in taking opportunities and competing effectively with other competitors.